Measuring organized crime: Statistical indicators and economics aspects - Carlo Capuano; Massimiliano Giacalone (Economics and Econometrics Research Institute (EERI), 2018)
One of the most negative factors that characterize Italian economy and society is the pervasive and oppressive presence of organized crime, affecting many aspects of the daily live and every sector of business. The data unfortunately show how this phenomenon is increasingly growing and involves more and more aspects of our society (Albanese & Marinelli, 2013). In recent years there have been peaceful demonstrations but also concrete acts by the police that has made numerous arrests and thwarted many robberies. (Calderoni, 2014). However, the work done in recent years is not sufficient to definitively delete organized crime (OC), even more difficult and targeted intervention by the institutions is needed in order to definitively resolve this question. (Fedeli et al., 2017; Visco of the Bank of Italy, 2014). This work introduces new indexes that measure and compare organized crime in different territories. We apply then to Italian provinces and we obtain a ranking at national level.
Keywords: O17; O30; C73; R11; K14; K42; 330; Crime severity rate; index of criminality; organized crime; territorial indicators; economic impact; average edictal penalties